Identification of dietary patterns by principal component analysis in schoolchildren in the South of Brazil and associated factors - Gabriela Rodrigues Bratkowski; Vanessa Backes; Maria Teresa Olinto; Ruth Liane Henn (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to identify dietary patterns (DP) and associated factors in first grade school-children in elementary schools in the South of Brazil. Methods: school-based cross-sectional study, with a non-probabilistic sample of 782 schoolchildren aged 6 to 8. Food intake was assessed by a food frequency questionnaire. DP were identified using the principal component analysis and the prevalence ratios were obtained by Poisson regression with a robust variance. Results: four DP were identified and accounted for 25.3% of the total variance: "fruit, vegetables and fish" (8.5%), "sweets and salty snacks" (7.0%), "dairy, ham and biscuits" (5.0%) and "common Brazilian food" (4.8%). After the adjustment, breakfast habit and lower frequency of meals in front of a screen increased the probability of adherence to a high consumption of DP of "fruit, vegetables and fish". The maternal schooling level was linearly and inversely associated with DP of "sweets and salty snacks" and "common Brazilian food", and positively related to the DP of "dairy, ham and biscuits". Schoolchildren with food inse-curity and sufficiently active had higher probability of adherence to DP of "common Brazilian food". Conclusions: four DP were identified and associated with food insecurity, maternal socioeconomic characteristics and schoolchildren's behavioral characteristics.